A Review on Pharmacological Management of Prameha Roga with special reference to Kwatha Kalpana Described in Brhat-Trayi (AYUSHDHARA, 2023)
Lifestyle diseases are becoming burning issues in today’s era of fast-food and junk-foods. One of such health issue has been addressed in this article which is Prameha having similar characteristics as Diabetes Mellitus. Prameha has been described in all Ayurvedic texts starting from Vedas. While the main three texts of Ayurveda i.e., Brhat-trayi viz. Caraka Samhita, Sushruta Samhita and Vagbhatta Samhita have detailed description of Prameha roga. The main Dosha involved in Prameha is Kapha and ten Dushya are engaged in its complex pathogenesis. Therefore, the main principle behind treatment is using all measures against Kapha dosha. Along with it various diet, drugs and regimen have been mentioned which acts against Medas. The effect of Kwatha Kalpana has been specially highlighted in the texts for management of Prameha. Kwatha Kalpana is one of the therapeutic measures in Ayurveda which is prepared by boiling various raw drugs with 8 times of water. It is then reduced down to 4 times. The drugs used in making of Kwatha Kalpana are mainly of Katu, Tikta, Kashaya rasa, Katu vipaka, Ushna guna and having Dipana, Pachana, Rasayan properties. Therefore, this article highlights the concept of Kwatha Kalpana used in Prameha and pharmacology behind it.